Experimental Study on Combustion and Vibration Characteristics of Low-Speed Marine Diesel Engine Fuelled with Biodiesel - Gang Wu; Yuan Yuhao; Jiang Guohe; Guo Hao; Zhang Zhe (Polish Maritime Research)
This study, conducted on a six-cylinder low-speed marine diesel engine (MAN 6S35ME-B9) test bench, systematically investigates the effects of biodiesel-diesel blends (B10, B30, B50) on combustion and vibration characteristics for the first time, addressing a research gap in this area. Using multi-sensor synchronised acquisition of in-cylinder pressure and vibration signals, combined with time-domain (RMS), frequency-domain (FFT), and continuous wavelet transform (CWT) analysis, the research reveals the combustion mechanisms and vibration response characteristics of biodiesel. The results show that biodiesel’s high cetane number and oxygen content advanced the peak in-cylinder pressure, with the maximum pressure increasing as the blend ratio increased. However, its lower heating value caused higher brake-specific fuel consumption (BSFC) than D100 fuel. Vibration analysis indicated that biodiesel’s RMS values were generally higher than D100’s, especially in the 1.0-1.75 kHz mid-frequency band, which is closely related to combustion impacts. Vibration changes in the high-frequency band (1.9-2.5 kHz) might stem from knocking or mechanical impacts, with vibration characteristics showing nonlinear patterns across different blend ratios. This study’s application of the CWT method to low-speed engine vibration analysis offers theoretical and experimental support for optimising biodiesel use in ship power systems and new ideas for combustion state monitoring and fault diagnosis based on vibration signals.